Master Plan Pit Blok Timur Tambang Batubara Di PT Artamulia Tatapratama Kabupaten Muaro Bungo Provinsi Jambi - Benget Harmoko Manik; Guskarnali Guskarnali; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2020)
PT Artamulia Tatapratama is a private coal mining company located in Tanjung Belit Village, Jujuhan, Muaro Bungo, Jambi Province. The topic of discussion in this research is the location in the East block has an area of 161 Ha, does not yet have a mining design, therefore a master plan is carried out, provided that the striping ratio of the company is 8 : 1, 10 : 1 and 12 : 1. The method begins with taking strike dip 80 data for landslide analysis and optimal angles with Dips software, followed by testing the safety factor in the Slide software, then processing 60 drill data on Minescape to design pit limits, calculating reserves using the strip block method and solid blokc, then resgraphic determining economical area is mined and designing the pit design. Based on this, there are indications of wedge avalanches, the design angle should not be more than 82o and the pit limit area of 98 Ha with a striping ratio design pit SR 8 area 22 Ha overburden 4.828.436 BCM coal 595.956 tons, pit design SR 10 area 35 Ha overburden 6.997.226 BCM and coal 690.022 tons, design pit SR 12 with an area of 42 Ha 9.702.861 BCM and coal 799.561 tons.